Rekonstruksi Pedagogi Pendidikan Agama Islam di Era Digital: Pengembangan Model Islamic Digital-Spiritual Pedagogy bagi Generasi Z: Reconstructing Islamic Religious Education Pedagogy in the Digital Age: Developing the Islamic Digital-Spiritual Pedagogy Model for Generation Z - Jusman Jusman; Rusmiaty Rusmiaty (Dirasat Islamiah: Jurnal Kajian Keislaman, 2026)
The rapid advancement of digital technology has transformed how students access religious knowledge, creating an urgent need to rethink Islamic Religious Education (IRE). However, prior studies have largely examined digital literacy, spirituality, and teacher competence as separate domains, resulting in the absence of an integrated pedagogical framework that explains their interrelationships. This study aims to synthesize existing research on the transformation of IRE in the era of technological disruption and to develop the conceptual model of Islamic Digital-Spiritual Pedagogy (IDSP). A Systematic Literature Review (SLR) combined with meta-synthesis was conducted following the PRISMA 2020 guidelines. The literature search was performed through Google Scholar, covering articles published between 2018 and 2026, with inclusion limited to national journals accredited by the Science and Technology Index (SINTA) and indexed in Garba Rujukan Digital (GARUDA). Following the selection and quality appraisal process, 38 articles met the inclusion criteria for analysis. The meta-synthesis identified three overarching themes: the transformation of Generation Z characteristics, the reconstruction of teachers’ roles, and the development of the IDSP model. The findings indicate that transforming IRE requires the integration of digital religious literacy, spiritual internalization, and teachers' transformative agency. Based on these findings, this study proposes the IDSP model, which conceptualizes digital technology as part of a pedagogical ecosystem shaping students' religious knowledge, religious identity, and spiritual experiences. The proposed model provides a conceptual foundation for curriculum development, teacher professional development, and future empirical research on IRE in the digital era.